The Pacitan State Community Academy's Interactive Promotional Media with the Implementation of Adobe Flash Player Action Script: Media Promosi Interaktiv Akademi Komunitas Negeri Pacitan Dengan Penerapan Action Sript Adobe Flash Player - Mochammad, syahrul; Prameswari, Citra Ratih; Kumala, Charisma Indra (Journal of Electrical, Electronic, Mechanical, Informatic and Social Applied Science, 2024)
Promotion is something that’s often heard when introducing a new product so that it can be known by the wider community. In the current technological era, the media used as a form of promotion have various models, such as posters, pamphlets and banners. The advantage of promotion using posters and banners is that it can save human resources to introduce a product by distributing it or sticking it on the wall. However, this also makes it difficult for readers to find words or images that are difficult to understand, so misperceptions often occur. Therefore, in this research the author will try to design a promotional media by applying the concept of interactive multimedia, where readers are enabled to communicate in two directions. This interactive media concept will be built with flash player platform technology that implements action scripts